Os resíduos medievais do corpo grotesco em Dona Flor e seus dois maridos, de Jorge Amado - Barbosa, Iêda Carvalhêdo (2024)
Jorge Amado (1912-2001) places the people at the centre of his own creative process, in a literature in which the people are actors and not just subjects. He is a writer who stands out as a national reference, due to the fact that his novels give relevance to Brazilian culture and for having tackled social and polemical themes. Furthermore, there is a desacralised art in amadian narratives, very connected to the people, which makes his work resemble the ‘carnivalized’ literature typical of the Middle Ages, investigated by Bakhtin (2010a), because, in addition to the malicious and provocative language, the ‘types’, scenarios and themes created by the Bahian author are traces of extra-official culture, characteristic of the aesthetics of contesting the rules of carnival, which make grotesque bodies appear that generate nonsense, the strange and invert meanings. In order to study these grotesque bodies, this paper seeks to analyze one of the most emblematic novels written by Amado, Dona Flor e seus dois maridos, with regard to the behaviour of the novel's main female character, Florípides, as well as the male protagonists who make up the love triangle, Vadinho and Teodoro, establishing their relationship with the medieval grotesque. Besides, we try to show the association between eating and loving through the dishes and recipes mentioned in the narrative, seeking to determine whether this relationship comes from the Middle Ages. It is also verified whether the use of vocabulary, especially with regard to sexual organs and activities in the book under examination, is similar to that used by the medieval popular classes. In the desire to understand how the medieval mentality about the grotesque is actively manifested in this novel, we applied Bakhtin's carnavalization and the Theory of Literary and Cultural Residuality, a theoretical-investigative proposal systematized by Roberto Pontes and certified by the Federal University of Ceará and the CNPq Research Directory, which uses the following operative concepts: residue, crystallization, imaginary, mentality, endoculturation and cultural hybridization. The analysis made it possible to verify that the grotesque is present in Dona Flor e seus dois maridos, mainly in the figures of the trickster Vadinho and dona Flor through their own names and their anti-normative attitudes, escaping the stability of hegemonic values and showing remnants of the medieval carnival mentality. Moreover, there is a clear association between food and sex in amadian narrative, resulting from the crystallization of this same relationship in the medieval period. It is also worth pointing out that the obscene language, full of swear words, present in the narrative under investigation, shows residual traces of the popular language of the Middle Ages, proving the anti-dogmatic and libertarian features of the characters.